Microbial ecology of aerial plant surfaces (CABI Publishing, 2006)
This book provides a description of the diverse inhabitats of plant surfaces, their interaction with the plant and each other, and the influence of factors such as ultraviolet radiation, nutrients endophytes epiphytes, and immigration on the composition of microbial communities